BRIDGING THE GAP BETWEEN USERS AND TECHNOLOGY: PERCEPTIONS OF EG4.0 OPAC SERVICES AT GOVT DIVISIONAL PUBLIC LIBRARY, KOTA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This research paper examines the perceptions, challenges, and usage patterns of users interacting with the eG4.0 Online Public Access Catalog (OPAC) services at the Government Divisional Public Library, Kota. With the increasing integration of digital tools in public libraries, understanding user attitudes toward such services is crucial for enhancing accessibility and usability. The study employs a mixed-methods approach, incorporating surveys and interviews with library patrons to assess their awareness, satisfaction levels, and barriers to effective OPAC utilization. Findings reveal a significant gap between users’ expectations and their ability to navigate the digital platform, often attributed to limited digital literacy and insufficient guidance. The paper also highlights best practices and suggests strategies to improve user engagement, including targeted training sessions, user-friendly interface enhancements, and proactive librarian support. By bridging the gap between users and technology, the library can ensure a more inclusive and effective digital experience for its patrons.